Effect of hydrogen impurities on hydrogen oxidation activity of Pt/C catalyst in proton exchange membrane fuel cells. Issue 1 (9th March 2023) - Qin, Yufeng; Sun, Chaoyong; Ke, Shaojie; Wen, Rou; Wang, Yifan; Ji, Jing; Dou, Meiling
Abstract: High-purity of hydrogen is vital to the guarantee of end usage in proton exchange membrane fuel cell (PEMFC) electric vehicles (EVs) with superior durability and low expense. However, the currently employed hydrogen, primarily from fossil fuel, still contains some poisoning impurities that significantly affect the durability of PEMFCs. Here, we investigate the poisoning effect of several typical hydrogen impurities (S 2–, Cl –, HCOO – and CO3 2– ) on the hydrogen oxidation reaction (HOR) of the state-of-the-art carbon-supported platinum (Pt/C) catalyst used in the PEMFC anode. Electrochemical results indicate that the electrochemically active surface area of Pt/C is hampered by these hydrogen impurities with reduced effective Pt reactive sites due to the competitive adsorption against hydrogen at Pt sites showing the extent of the poisoning on Pt sites in the order: S 2– > Cl – > HCOO – > CO3 2– . Density functional theory calculations reveal that the adsorption energy of S 2– on Pt (111) is greater than that of Cl –, HCOO – and CO2, and the electronic structure of Pt is found to be changed due to the adsorption of impurities showing the downshift of the d-band centre of Pt that weakens the adsorption of hydrogen on the Pt sites. This work provides valuable guidance for future optimization of hydrogen quality and also emphasizes the importance of anti-poisoning anode catalyst development, especially towards H2 S impurities that seriously affect the durability of PEMFCs. Abstract : Theoretical and experimental studies are carried out on the poisoning effect of several typical hydrogen impurities on the hydrogen oxidation reaction of the state-of-the-art carbon-supported platinum catalyst used in the anode of proton exchange membrane fuel cells. Graphical Abstract: